Optimalisasi Fungsi Sarana Prasarana Pendidikan Jasmani dalam Perkembangan Motorik Anak Kelas 1 SDN 2 Sadang - Ihsanuddin, Biqi; , Drs. Mulyadi S. K., SH.,M.Pd (2017)
Facilities and infrastructure are used in teaching physical education often ignores the motor development of children, so that the delivery of learning materials is less than optimal. This type of research uses qualitative research with phenomenological research design. Data collection techniques used in this study were interviews, observation, and documentation. Data analysis techniques in this research is data reduction, data presentation, and draw conclusions. By understanding the function of physical education facilities and infrastructure in SDN 2 Sadang, teachers can make innovation in learning so that teachers are able to pay attention to the suitability of facilities and infrastructure to the level of motor development of students. In addition this study can help the teacher to know the results optimalisasia infrastructure function and motor development of students. Keywords: facilities, infrastructure optimization, motor development